Development and characterisation of a flexible valve timing system towards optimised performance of small internal combustion engines - Hanipah, M. Razali; Jafferi, Jamaludin; Heerwan, P. M.; Mohamed, Zamri; Abdullah, Abdul Adam (2017)
-